Economic stagnation and development aid - Emil Küng (Intereconomics, 1976)
The main objectors to a link being established between special drawing rights (SDRs) and the financing of development have in the past been the industrial countries. They have been pointing out that SDRs were created for other purposes — more effective control over international liquidity — and that a link with development finance would have an inflationary effect. If however the present unemployment situation in the industrial countries should become at least partly a permanent feature the idea of such a link would become more attractive than hitherto — to the industrial countries.
Keywords: 330; Development Policy